Glucan rich nutrition does not increase gut translocation of beta‐glucan. Issue 1 (21st November 2020) - Hoenigl, Martin; Lin, John; Finkelman, Malcolm; Zhang, Yonglong; Karris, Maile Y.; Letendre, Scott L.; Ellis, Ronald J.; Burke, Leah; Richard, Byron; Gaufin, Thaidra; Isnard, Stéphane; Routy, Jean‐Pierre; et al.
Abstract: Background: (1‐3)‐b‐D‐glucan (BDG) is a fungal cell wall component and, in the absence of invasive fungal infection, a novel biomarker for microbial translocation of endogenous fungal products from the gastrointestinal tract into systemic circulation. However, its value as a marker of fungal translocation is limited by a concern that plant BDG‐rich food influences blood BDG levels. Methods: We conducted a pilot clinical trial to evaluate the impact of a standardised oral BDG challenge on blood BDG levels in participants with and without elevated microbial translocation. We enrolled 14 participants including 8 with HIV infection, 2 with advanced liver cirrhosis, and 4 healthy controls. After obtaining a baseline blood sample, participants received a standardised milkshake containing high levels of BDG followed by serial blood samples up to 8 hours after intake. Results: The standardised oral BDG challenge approach did not change the blood BDG levels over time in all participants. We found consistently elevated blood BDG levels in one participant with advanced liver cirrhosis and a single person with HIV with a low CD4 count of 201 cells/mm 3 . Conclusion: Our findings indicate that BDG blood levels were not influenced by plant origin BDG‐rich nutrition in PWH, people with advanced liver cirrhosis, or healthy controls. Future studies are needed to analyse gut mycobiota populations in individuals with elevated blood BDG levels.